Task-Based Needs Analysis: Identifying Gaps Between Cultivation Scheme of BE MA Program and Market Demands: A Case Study of GDUFS BE Program - Yilin Xu, (Advances in Social Sciences Research Journal, 2023)
Cultivation scheme is the foundation of the teaching. With an increasing demand of professional English talents, needs analysis of market demands has become a significant basis for the development of Business English teaching. Despite the growing popularity of Business English (BE), needs analysis combining cultivation scheme and markets demands has rarely been carried out. Based on the the cultivation scheme of BE MA program of Guangdong University of Foreign Studies (GDUFS) and wants ads collected online, this study aims to identify gaps between the cultivation scheme and market demands in Guangdong. Adopting the Key to employability Model and competence model, the present study investigates the following three questions: (1) what is the market demands for professional BE talents? (2) Is there a gaps between the overall cultivation scheme of BE MA programs in GDUFS and the market demands for BE talents? If there is a gaps, what’s the discrepancy between the cultivation scheme of BE MA program and the market demands and how to improve the current cultivation scheme? (3) How to realize the program mission of the modified cultivation scheme? The results reveal that objectives of GDUFS BE Postgraduates program cultivation scheme should be improved and can be modified according to the General Model of BE Postgraduates’ Abilities. Some practical suggestions regarding the revision and realization of the cultivation scheme of BE MA program of GDUFS are put forward. The research results have reference value for universities to adjust their orientations to meet the market demands.